Being Exposed to Covid-19 During Pregnancy : A Qualitative Study in North Halmahera, Indonesia - Tauho, Kristiani Desimina; Diba, Jane Angelita (Babali Publisher, 2024)
Introduction: Pregnant women are vulnerable to COVID-19 due to reduced partial immunity commonly occurring during pregnancy. Rarely has research reported how pregnant women deal with COVID-19. This study explores the experiences of pregnant women confirmed with COVID-19. Methods: This qualitative study utilized a phenomenological approach. Six postpartum mothers living in North Halmahera, Mollucas, participated in the research. Data analysis was carried out using the Colaizzi method. Results: The participants were positively confirmed with COVID-19 in the third trimester of pregnancy. The perceived symptoms included cough, cold, fever, shortness of breath, headache, dizziness, and loss of smell and taste. The perceived feelings varied among participants. One participant reported worries about her fetus's condition, and another felt disappointed because she could not care for herself, leading to infection. Two participants did not feel panic or fear because the symptoms were mild, and they had previously treated other family members infected with COVID-19. Conclusion: To improve their healing, the research participants tried to remain strong, adhere to health protocols, maintain a healthy diet, take medicine, think positively, and practice dhikr and sholawat. These findings can be used to improve the quality of care.